Financial Reporting Quality, Political Connectedness, and Monitoring Mechanisms: Evidence from Saudi Arabia - Alsalhi, Faisal Saleh (Curtin University, 2022)
This study investigates the associations between financial reporting quality, political connectedness, and monitoring mechanisms (namely, strategic institutional ownership, internal audit sourcing arrangements, and audit quality) in Saudi Arabia. The study builds on a multi-theoretical framework to develop its hypotheses. Using 899 non-financial firm-year observations listed on the Saudi Capital Market between 2009 and 2017, findings show that political connectedness and strategic institutional investors enhance the quality of financial reports in the Saudi Arabian context.